Code Mixing in EFL Classroom: Views from English Teachers Side - Agus Rahmat (Al-Lisan: Jurnal Bahasa, 2020)
The objectives of this research were to find out the category of code mixing used by the English teacher and the code mixing category dominantly used by the English teacher in teaching EFL (English as a foreign language) classroom based on the category of code mixing according to Muysken (2000). This research employed descriptive qualitative research design to analyze the teacher’s code mixing in teaching EFL at SMK Negeri 1 Makassar. The participant of this research was one of all the English teacher of SMK Negeri 1 Makassar, this participant was taken by using purposive sampling technique. The instruments of this research were observation and audio recording.The result showed that (1) The English teacher of SMK Negeri 1 Makassar used all of the categories that categorized by Muysken (2000, cited in Liu, 2008: 6) in teaching EFL classroom, they were: Insertion, Alternation and Congruent Lexicalization. There were seventeen examples of Insertion category, two examples of Alternation category and there were also two examples of congruent lexicalization category used by the English teacher; (2) The category of code mixing dominantly used by the English teacher of SMK Negeri 1 Makassar was insertion category in teaching EFL classroom.Therefore, it can be a positive input of the English teachers to enrich their English vocabulary to avoid using code mixing in teaching EFL classroom.